Sexual Orientation in Individuals With Congenital Adrenal Hyperplasia: A Systematic Review - Daae, Elisabeth; Feragen, Kristin Billaud; Waehre, Anne; Nermoen, Ingrid; Falhammar, Henrik (Frontiers in Behavioral Neuroscience, 2020)
Congenital adrenal hyperplasia (CAH) is a spectrum of genetic disorders causing deficiencies in the steroidogenic enzymes in the adrenal cortex normally leading to variable degrees of cortisol and aldosterone deficiency as well as androgen excess. Exposure of androgens prenatally might lead to ambiguous genitalia. The fetal brain develops in traditional male direction through a direct action of androgens on the developing nerve cells, or in the traditional female direction in the absence of androgens. This may indicate that sexual development, including sexual orientation, are programmed into our brain structures prenatally. The objective of this study was to perform a systematic review of the literature, investigating the sexual orientation in patients with CAH. The study also aimed at assessing the measures used across studies to define sexual orientation. The review is based on articles identified through a comprehensive search of the OVIDMedline, PsycINFO, CINAHL, and Web of Science databases published up to May 2019. All peer-reviewed articles investigating sexual orientation in people with CAH were included. Quantitative, qualitative, and mixed methods were considered, and no age or language restrictions were imposed on the investigated publications. Self-report, parent-report, and third-party reports were all included. The present review included 30 studies investigating sexual orientation in patients with CAH both assigned female at birth (46,XX) (n=927) and assigned male at birth (46,XY and 46,XX) (n=274). Results indicate that assigned females at birth (46,XX) with CAH are less likely to have an exclusively heterosexual orientation than women from the general population, whereas no assigned males at birth (46,XY or 46,XX) with CAH identified themselves as non-heterosexual. There was a wide diversity in the measures used and a preference for unvalidated and self-constructed interviews. Hence, the results need to be interpreted with caution. Methodological weaknesses in the measures used might have led to non-heterosexual orientation being overestimated or underestimated. The methodological challenges identified by this review should be addressed in future research.